Strategi Cerita Berantai sebagai Metode Pembelajaran untuk Meningkatkan Keterampilan Berbicara Siswa SD - Kholiq, Muhammad Aji Abdul; Ismiyanti, Yulina; Yustiana, Sari (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
Speaking skills are a fundamental component of students’ communication development; however, they are often overlooked in elementary school instruction. This study investigates the effectiveness of the chain storytelling strategy in enhancing the speaking skills of third-grade students at SDN Waru. Employing a qualitative case study design, data were collected through observation, interviews, and documentation. Data analysis followed the processes of data condensation, data display, and conclusion drawing, as suggested by Miles and Huberman. The results indicate that the chain storytelling strategy positively influences students’ speaking abilities. It encourages active participation in oral communication, improves articulation and diction, reduces anxiety about speaking in front of peers, and enhances creativity in narrative construction. These findings align with Vygotsky’s social constructivist theory, which underscores the role of social interaction in learning, and Rogers’ (2003) diffusion of innovations theory, which explains how new strategies are adopted in educational settings. This study highlights the necessity of employing interactive learning strategies and the importance of a supportive classroom environment in fostering students' speaking confidence. It recommends targeted training for teachers in implementing innovative methods and suggests further research involving a broader scope and larger sample to validate and expand upon these findings.